Investigations of Nanoscale Defects in Crystalline and Powder ZnSe Doped With Fe for Laser Application. Issue 4 (17th October 2017) - Gavrishchuk, Evgeny; Zykova, Marina; Mozhevitina, Elena; Avetisov, Roman; Ikonnikov, Vladimir; Savin, Dmitry; Rodin, Sergey; Firsov, Konstantin; Kazantsev, Sergey; Kononov, Igor; Avetissov, Igor
Abstract : The theoretical and experimental analysis of the ternary system Zn‐Se‐Fe for obtaining new fundamental information on phase using X‐ray analysis and inductively coupled plasma mass‐spectrometry is carried out. New experimental data of isothermal annealing in the Zn‐Se‐Fe system at the temperatures 730, 814, 1073 K by X‐ray studies confirms the reliability of theoretical isothermal sections. The information on Fe solubility and concentrations of native point defects of atomic scale at bi‐ and monovariant conditions at 1073 and 1273 K have been carried out. Taking into account the new data on phase equilibria, it is possible to fabricate active ZnSe:Fe 2+ elements to create an effective laser operating at the temperature of 300 K with 1.52 Joule emission energy with efficiency of ≈50% relative to the absorbed energy. Abstract : On the basis of theoretical and experimental analysis of the ternary system Zn‐Se‐Fe, it was possible to fabricate active ZvSe:Fe 2+ elements, to create an effective laser operating system at the temperature of 300 k with 1.52 Joule emission energy with an efficiency of ≈50% relative to the absorbed energy.